The distinctiveness of Marxist conception of alienation. Issue 3 (2nd October 2021) - Kumar, Pankaj
Abstract : To understand the Marxist conception of alienation, this paper is divided into two interrelated parts. The first part shall deal with the distinctiveness of the Marxist conception of alienation from its rival conceptions. It proposes that in Marx's formulation, alienation is a distinctively modern phenomenon that should not be understood merely as an ethical or moral critique of capitalism. Besides, it also outlines the core of alienation. The second part of the paper deals with the major critiques of the Marxist conception of alienation. It takes up the controversy surrounding the place of alienation in the overall system of Marx's writings. It revolves around two key debates. First, whether or not alienation remained the constant pre-occupation of Marx throughout his writings? Second, does Marx's theory of alienation presuppose an essentialist/meta-historical conception of human nature?